2021
DOI: 10.1155/2021/9932088
|View full text |Cite
|
Sign up to set email alerts
|

The High Expression of PTPRH Is Associated with Poor Prognosis of Human Lung Adenocarcinoma

Abstract: Objective. The aim of the study is to explore the prognosis value of PTPRH in patients with lung adenocarcinoma (LUAD). Methods. Oncomine, UALCAN, and GEPIA databases were employed to examine the differential expression of PTPRH between LUAD and adjacent tissues. 100 pairs of LUAD and adjacent tissue samples were involved in this study. qRT-PCR and immunohistochemical staining were performed. Meanwhile, we analyzed The Cancer Genome Atlas (TCGA) data to investigate the correlation between PTPRH gene expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…Existing studies have reported the relationship between PTPRH and LUAD. For example, Chen et al [ 31 ] observed that PTPRH was overexpressed in the LUAD tissue and served as an independent prognostic factor for LUAD. Previous studies indicated the prognostic value of regulator of G protein signaling 20 (RGS20) in patients with LUAD, and it might be a novel prognostic marker for LUAD [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies have reported the relationship between PTPRH and LUAD. For example, Chen et al [ 31 ] observed that PTPRH was overexpressed in the LUAD tissue and served as an independent prognostic factor for LUAD. Previous studies indicated the prognostic value of regulator of G protein signaling 20 (RGS20) in patients with LUAD, and it might be a novel prognostic marker for LUAD [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…[54] Study had shown that PTPRH was correlated with a poor prognosis in LUAD patients. [55] TNS4 is a putative oncogene in LUAD and gastric cancer. [56,57] In many cancers, we can detect abnormal MET tyrosine kinase receptor signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al once validated the prognostic value of PTPRH in LUAD tissues. The transcription as well as the protein level of PTPRH was found to be noticeably upregulated in LUAD tissues, as demonstrated by qRT-PCR and immunohistochemistry, respectively [ 40 ]. The role of DKK1 in cancer development remains unelucidated.…”
Section: Discussionmentioning
confidence: 99%